A route for an improved hydrogen sensing window using ZnO decorated Pt/AlGaN/GaN HEMT sensors - Kim, Se Eun; Jang, Seo Young; Park, Kyung Ho; Lee, Sang Woon (Ceramics International, 2022)
H2 has received considerable attention as an alternative energy source. The detection of H2 is necessary for its safe use due to its explosive flammability. Pt/AlGaN/GaN HEMT can detect H2 gas by a shift in the threshold voltage (Vth) induced by the formation of a dipole layer upon H2 exposure. However, using the Pt/AlGaN/GaN HEMT, the change of Vth after H2 exposure is as small as ∼0.35 V, indicating a narrow sensing window (ΔVth) for H2 detection. This can cause a detection failure in the case of a dynamically fluctuating gas over time. Here, we demonstrate a significantly widened sensing window of ΔVth (1.8 V) using an extremely thin (∼1 nm) ZnO layer grown by atomic layer deposition on the Pt/AlGaN/GaN HEMT sensors. The enlarged sensing window of ΔVth originated from a decreased work function of ZnO on the Pt gates, which further shifted Vth in the negative direction and led to the formation of a dipole layer upon H2 exposure.
Keywords: AlGaN/GaN HEMTs; AlGaN/GaN-HEMT; Alternative energy source; Atomic-layer deposition; Detection of H; Hydrogen-sensing; Sensing windows; ZnO layers; AlGaN; HEMT; Hydrogen; Sensing window; ZnO